Guatemala : Country Financial Accountability and Procurement Assessment Report (CFAA/CPAR) - World Bank (Washington, DC, 2012)
This Country Financial Accountability and Procurement Assessment Report (CFMCPAR) analyzes the Government's fiduciary responsibility to manage public resources through transparent institutions and efficient systems of budgeting and procurement. Accordingly, the recommendations contained in this report seek to identify areas where public financial management (PFM) can be improved with the goal of strengthening fiscal discipline. Chapter 2 describes the PFM legal and institutional framework, Chapter 3 looks into the process of budget formulation and its reliability, Chapter 4 examines treasury and budget execution management, Chapter 5 discusses procurement management, Chapter 6 evaluates the arrangements for fiscal reporting and external oversight, and Chapter 7 presents the main conclusions and suggests priorities for action.